Study of the Impact of Chronic Obstructive Pulmonary Disease on Vocal Function - Elshebl, Omnia Zakaria; Mohamed, Asmaa Eldesouky; Ahmed, Salwa Ahmed Abdelhay (International Archives of Otorhinolaryngology, 2025)
Chronic obstructive pulmonary disease (COPD) affects lung function, but its impact on vocal function remains understudied.To investigate the relationship involving COPD severity and vocal acoustic parameters and to assess the correlations regarding acoustic measures and pulmonary function tests in clinically stable COPD patients.The present observational study included 40 COPD patients diagnosed according to the 2023 guidelines of the Global Initiative for Chronic Obstructive Lung Disease (GOLD). All patients underwent spirometry, an otorhinolaryngological examination, and acoustic voice analysis, including fundamental frequency (F0), harmonics-to-noise ratio (HNR), jitter, and shimmer. The Arabic version of the Voice-Related Quality of Life (V-RQOL) questionnaire was used to assess voice-related impairment.The sample had a mean age of 65 ± 6 years, with 92.5% of male subjects. Dysphonia was observed in 57.5% of the patients. Laryngoscopic findings included Reinke's edema (42.5%), laryngitis (25%), polypoid degeneration (20%), and phonasthenia (12.5%). The acoustic analysis revealed significant negative correlations involving pulmonary function parameters and vocal measures. The regression analysis demonstrated forced expiratory volume in the first second (FEV1) and FEV1/forced vital capacity (FVC) as significant predictors of mean pitch, jitter, and shimmer, with each unit increase in FEV1 associated with a decrease in these acoustic measures (p < 0.001).The severity of COPD is significantly associated with acoustic voice alterations, with disease progression leading to measurable impairments in vocal function. These findings highlight the importance of voice assessment in COPD management.
Keywords: COPD; voice quality; pulmonary function; acoustic analysis; GOLD classification